A Comparative Study on the Performance of Stock Market and Mutual Funds During Bullish and Bearish Period - Dharmaraj, C.; Santhosh, Esme (Indian Journal of Finance, 2010)
Indian stock market is subject to many fluctuations. Stock market becomes bearish and bullish in response to various economical, political, social and international factors. Stock markets provide huge profits for the investors and at the same time, they are very risky due to these fluctuations. The investors can take advantage of profitable investments in stock market and lower their risk by means of investing in Mutual Funds but Mutual Funds also have certain risk element in it, hence taking risks is inevitable for an investor. Risk involved in investments can be minimized by knowing the right type of investment suitable for a particular period. In this study, sharpe ratio is used to compare the Performance of Stock Market and Mutual Funds during the Bullish and Bearish Period. This study also will help the investors in choosing either Mutual Funds or Stock market investments according to the nature of the market (bullish or bearish) to maximize the return and minimize the risk.